BIOShLAMLARNI QAYTA IShLASh VA SUYUQ FOSFORLI ORGANIK O‘G‘IT TAYYORLASh - Jamayeva, N.R.; Raximov, U.U. (SCIENCE and SOCIETY, 2025)
In this study, sewage sludge generated during wastewater treatment was fermented to obtain liquid organic phosphorus fertilizer. The results showed that PO4 and TDS indicators were analyzed, and some samples were identified as suitable for use as fertilizer.
Keywords: biosolids; organic fertilizer; phosphorus fertilizer; nitrogen (N); phosphorus (P); potassium (K); microelements; fermentation; aerobic process; anaerobic process; pH control; total dissolved solids (TDS); phosphate (POX)